Barleria prionitis L.: An Illustrative Traditional, Phytochemical and Pharmacological Review - Banerjee, Sabyasachi; Banerjee, Subhasis; Jha, Gaurab K.; Bose, Sankhadip (Natural Products Journal, The, 2021)
Barleria prionitis, a small perpetual, prickly shrub, belongs to the family Acanthaceae, normally called “porcupine flower” or “Vajradanti” with a lot of vernacular names. It is an indigenous herb of Southern Asia and some regions of Africa. The therapeutic use of leaf, flower, stem, seed, shoot, root and in certain cases complete herb of B. prionitis against numerous disorders including cough, fever, jaundice, asthma, severe pain, acne, cut wound is recognized by ayurvedic and other conventional medicinal systems. An exhaustive bibliographic research of this plant has been carried out by means of scientific engines and databases like Google Scholar, PubMed, and Science direct; as a result, it has been found that this herb possesses a rich phytochemical content and a wide range of pharmacological activities such as antimicrobial activity, anthelmintic activity, antidiarrheal activity, antioxidant activity, antifertility activity, anti-diabetic activity, anti-inflammatory activity, cytoprotective activity, antiarthritic activity, diuretic activity, hepatoprotective activity, enzyme inhibitory activity and antinociceptive activity without any toxic effects. The plant has been reported to have tannin, saponin, flavonoid, glycoside, alkaloid and phenolic compounds present in it. It is also a noteworthy origin of secondary metabolites such as β-sitosterol, lupeol, syringic acid, and vanillic acid. However, having potential therapeutic importance, it is still underutilized.
Keywords: anthelmintic